General Practitioners' experience of child and adolescent suicidal ideation and behaviour – a survey. (2nd November 2015) - Kolshus, E. M.; Kolshus, E. H.; Gavin, B.; Cullen, W.; McNicholas, F.
Abstract : Objectives: A major cause of death in Irish men aged 15–24 is suicide and the rates for those aged 15–19 are amongst the highest in Europe. Despite concerns over suicidal ideation or behaviour, little research has been done in the Irish primary care context. We therefore aimed to carry out a study of Irish General Practitioners (GPs)' experience regarding suicidal ideation or behaviour in children and adolescents. Methods: The study design was a descriptive, cross-sectional, questionnaire survey. We randomly selected 480 GPs and invited them to participate via post. Results: In total, 198 GPs replied, representing a response rate of 41% with a sampling error of ±6.8%. In total, 184 of respondents (93%) saw more than 50 children and adolescent patients annually, however, presentations of suicidal ideation and behaviour were relatively rare, with 36% reporting seeing none, 58% seeing between one and five and 6% seeing more than five such presentations annually. In total, 119 (62%) of GPs reported a willingness to prescribe antidepressants for this age group. In total, 66% of GPs felt this was either 'always' or 'usually' a difficult patient group to manage, and the single most commonly reported difficulty by GPs was access to services [ n =48 (33%)]. Conclusions: GPs reported that their management of children and adolescents with suicidal ideation or behaviour is often difficult. GPs play a key liaison role in the area of child and adolescent mental health, but our results indicate that GPs are also involved in the treatment of this patient group. However, ongoing education was not a priority according to GPs themselves.